Monitoramento do fluxo de água, sedimentos e solutos em uma bacia hidrográfica agrícola no sul do Brasil - Dambroz, Alice Prates Bisso (2024)
Effective management and protection of natural resources especially soil and water require a thorough understanding of hydrological processes in a catchment. In South Brazil, the 18.5 km2 Guarda Mor catchment, characterized by strong topographic gradients, is vulnerable to soil and water degradation, with much of its land use under no-till agriculture. Situated at the transition between volcanic to sedimentary lithologies and featuring an escarpment with a near 300-meter altitude difference, this catchment is part of a fluvial system which was heavily and unprecedently impacted by extreme rainfall and flooding in April and May 2024. To quantify and analyze the catchment! s hydrological behavior, we combined traditional hydrological monitoring of rainfall, streamflow, sediment, and solute (calcium, magnesium, potassium, and phosphorus) concentrations with tools for hydrograph separation, hysteresis analysis, and sediment source tracing. This approach allowed us to examine both water quantity and quality over years of contrasting precipitation, during and in between rainfall events. Hydrograph separation of daily streamflow into fast and slow flow components was conducted using a digital filter and five models. For event-based analysis, dissolved calcium and magnesium concentrations were used as tracers in an end-member mixing analysis. We also assessed the hysteresis between of streamflow discharge and sediment and solute concentrations, calculated sediment and nutrient yields, and used sediment fingerprinting technique to estimate the main sediment sources based on land use. Streamflow varied considerably (average 3.14 m3 s-1 and peak of 183.45 m3 s-1), influenced by La Niña-induced droughts and El Niño-driven heavy rainfall, with extreme rainfall events recorded in 2023 and 2024. Baseflow indexes show that wetter periods and extreme events significantly impacted fast flow, although slow flow contributed to nearly half the total streamflow over time. Our analysis highlights the vulnerability of the sedimentary portion of the catchment to contributing to streamflow during rainfall events. Extreme events were responsible for most of the sediment yield, with one event in November 2023 yielding 18% of the monitored total (∼10, 400 tons) between 2020 and 2024. Crop fields were estimated as the main sediment source (44%), followed by stream channels (31%) and unpaved roads (25%). Total potassium concentrations were linked to runoff volume, while total phosphorus concentrations were correlated to sediment yield. During a drought period, between August 2022 and April 2023, increases in phosphorus concentrations impacted water quality. These findings are crucial for planning of sustainable strategies that preserve the hydrological functions of headwater catchments and mitigate the impacts of extreme floods or droughts. Furthermore, it demonstrates the importance of consistent, continuous, long-term monitoring for understanding catchment dynamics and supporting future management decisions.